Associations of Body Mass Index and Waist Circumference in Young Adulthood with Later Life Incident Diabetes. - Nair, Nandini; Vittinghoff, Eric; Pletcher, Mark J; Oelsner, Elizabeth C; Allen, Norrina B; Ndumele, Chiadi E; West, Nancy A; Strotmeyer, Elsa S; Mukamal, Kenneth J; Siscovick, David S; Biggs, Mary L; Laferrère, Blandine; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: The independent contribution of young adult exposure to overweight and obesity to later-life incident diabetes is not well studied. OBJECTIVE: To assess the associations of exposures to elevated body mass index (BMI) and waist circumference (WC) in young adulthood (ages 18-39 years) with incident diabetes later in life (≥40 years). DESIGN: Pooled data from 6 US prospective cohorts (Atherosclerosis Risk in Communities Study, Cardiovascular Risk Development in Young Adults Study, Cardiovascular Health Study, (4) Framingham Heart Study Offspring Cohort, (5) Health, Aging and Body Composition Study, and (6) Multi-Ethnic Study of Atherosclerosis. SETTING: Population-based cohort studies. PARTICIPANTS: 30 780 participants (56.1% female, 69.8% non-Hispanic white) without a diagnosis of diabetes by age 40. INTERVENTIONS: We imputed BMI and WC trajectories from age 18 for every participant and estimated time-weighted average exposures to BMI or WC during young adulthood and later life. MAIN OUTCOME MEASURE(S): Incident diabetes defined as fasting glucose ≥126 mg/dL, nonfasting glucose ≥200 mg/dL, or use of diabetes medications. RESULTS: During a 9-year median follow-up, 4323 participants developed incident diabetes. Young adult BMI and WC were associated with later-life incident diabetes after controlling for later-life exposures [hazard ratios (HR) 1.99 for BMI ≥ 30 kg/m2 and 2.13 for WC > 88cm (women)/>102cm (men) compared to normal ranges]. Young adult homeostatic model of insulin resistance mediated 49% and 44% of the association between BMI and WC with later-life incident diabetes. High-density lipoproteins and triglycerides mediated a smaller proportion of these associations. CONCLUSIONS: Elevated BMI and WC during young adulthood were independently associated with later-life incident diabetes. Insulin resistance may be a key mediator.
Keywords: Adolescent; Adult; Biomarkers; Body Mass Index; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Male; Obesity; Overweight; Prognosis; Prospective Studies; Risk Factors; United States; Waist Circumference; Young Adult